Protocol for whole-tissue immunolabeling, optical clearing, and lightsheet imaging of c-Fos protein expression in unsectioned mouse brains - Koukou Fu; Jing Yang (STAR Protocols)
Summary: The c-Fos protein has been broadly utilized as a marker of neuronal activity, and conventional immunohistochemistry to determine its expression relies on tissue sections. Here, we present a protocol to visualize the endogenous c-Fos protein in intact, unsectioned mouse brains responding to specific stimuli based on the immunolabeling-enabled three-dimensional imaging of solvent-cleared organs (iDISCO) method. We describe steps for tissue harvesting, fixation, decolorization, and permeabilization followed by whole-tissue anti-c-Fos immunolabeling. We then detail procedures for tissue embedding and optical clearing for imaging by lightsheet microscopy.For complete details on the use and execution of this protocol, please refer to Chen et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.